Is a computer feeder necessary in the dry lot cow? - Kube, J.C.; Shirley, John E.; Frantz, K.D. (Kansas Agricultural Experiment Station, 2012)
Springing heifers and dry cows were introduced to a computer feeder either 2 wk before their estimated freshening date or at calving. There was no significant difference in milk production, percentage milk fat, percentage milk protein, or somatic cell count (SCC). Lead feeding with a computer feeder resulted in a 40% decrease in concentrate consumption over bunk feeding during the dry period.
Keywords: Dairy; Somatic cell count; Lactation; Feed cost